Phosphorus in agricultural soils: drivers of its distribution at the global scale. (15th February 2017) - Ringeval, Bruno; Augusto, Laurent; Monod, Hervé; van Apeldoorn, Dirk; Bouwman, Lex; Yang, Xiaojuan; Achat, David L.; Chini, Louise P.; Van Oost, Kristof; Guenet, Bertrand; Wang, Rong; Decharme, Bertrand; et al.
Abstract: Phosphorus (P) availability in soils limits crop yields in many regions of the World, while excess of soil P triggers aquatic eutrophication in other regions. Numerous processes drive the global spatial distribution of P in agricultural soils, but their relative roles remain unclear. Here, we combined several global data sets describing these drivers with a soil P dynamics model to simulate the distribution of P in agricultural soils and to assess the contributions of the different drivers at the global scale. We analysed both the labile inorganic P (PILAB ), a proxy of the pool involved in plant nutrition and the total soil P (PTOT ). We found that the soil biogeochemical background corresponding to P inherited from natural soils at the conversion to agriculture (BIOG) and farming practices (FARM) were the main drivers of the spatial variability in cropland soil P content but that their contribution varied between PTOT vs. PILAB . When the spatial variability was computed between grid cells at half‐degree resolution, we found that almost all of the PTOT spatial variability could be explained by BIOG, while BIOG and FARM explained 38% and 63% of PILAB spatial variability, respectively. Our work also showed that the driver contribution was sensitive to the spatial scale characterizing the variability (grid cell vs. continent) and to the region of interest (global vs. tropics for instance). In particular, the heterogeneity of farming practices between continents was large enough to make FARM contribute to the variability in PTOT at that scale. We thus demonstrated how the different drivers were combined to explain the global distribution of agricultural soil P. Our study is also a promising approach to investigate the potential effect of P as a limiting factor for agroecosystems at the global scale. Abstract : Numerous processes drive the global spatial distribution of phosphorus (P) in agricultural soils, but their relative roles remain unclear. Thanks to a modelling approach, we found that almost all of the global spatial variability in total soil P in cropland soils (PTOT ) could be explained by the distribution of the soil biogeochemical background (that determines the P content of soils at the conversion to agriculture, BIOG), while both BIOG and farming practices (FARM) explained the spatial variability in inorganic labile P (PILAB ) ( 40% and 60%, respectively).